2016
DOI: 10.3102/0034654316652942
|View full text |Cite
|
Sign up to set email alerts
|

A Century of Progress

Abstract: The history of research on interventions for struggling readers in Grades 4 through 12 dates back to 19th-century case studies of seemingly intelligent children who were unable to learn to read. Physicians, psychologists, educators, and others were determined to help them. In the process, they launched a century of research on a wide variety of approaches to reading intervention. As shown in this systematic narrative review, much has changed over time in the conceptualization of reading interventions and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 172 publications
3
29
0
Order By: Relevance
“…however, we believe that it is important to note that explicit vocabulary instruction in the intervention did improve students' knowledge of words taught in the intervention and these practices could be beneficial for this population of students. Interventions that target vocabulary typically have large effects on vocabulary outcomes for adolescent struggling readers (Scammacca et al, 2015;2016), and our finding is in line with previous studies of vocabulary instruction for older students with difficulties.…”
Section: Vocabularysupporting
confidence: 92%
“…however, we believe that it is important to note that explicit vocabulary instruction in the intervention did improve students' knowledge of words taught in the intervention and these practices could be beneficial for this population of students. Interventions that target vocabulary typically have large effects on vocabulary outcomes for adolescent struggling readers (Scammacca et al, 2015;2016), and our finding is in line with previous studies of vocabulary instruction for older students with difficulties.…”
Section: Vocabularysupporting
confidence: 92%
“…For one, publication year was associated with fidelity reporting, with results indicating fidelity reporting increased over time. This finding was expected given the quality of educational research methodology has improved over time (Scammacca et al 2016; Vaughn and Swanson 2015). It also aligns with the previous research showing that syntheses conducted more recently (Swanson et al 2011; Wheeler et al 2006) found higher numbers of treatment fidelity reported than earlier syntheses (Gresham et al 1993; Gresham et al 2000).…”
Section: Discussionmentioning
confidence: 80%
“…These consistently strong impacts for reading interventions have not continued beyond Grade 3 with findings for students in the upper elementary (e.g., James-Burdumy et al, 2012;Scammacca et al, 2015;Wanzek & Roberts, 2012;Wanzek et al, 2010) and secondary grades (e.g., Cheung et al, 2016;Kemple et al, 2008;Lang et al, 2009;Scammacca et al, 2015Scammacca et al, , 2016 yielding typically smaller effects. A meta-analysis of reading interventions for students in fourth grade and beyond (Scammacca et al, 2015) reported an overall mean effect (d) of 0.49 for all measures and 0.21 for standardized measures across 82 study-wise effect sizes.…”
mentioning
confidence: 97%